Consumer ODR Governance Model for Enforceable Redress in Indonesia’s Digital Trade Framework - Elyani; Ramlan; Surya Perdana (Jurnal Wawasan Yuridika, 2025)
The growth of digital transactions has increased consumer disputes and created the need for fast, affordable, accountable, and enforceable redress mechanisms. This article examines the regulatory gaps in consumer online dispute resolution within Indonesia’s digital trade framework and makes enforceable procedural standards for consumer redress. This study employs doctrinal legal research using statutory, conceptual, and limited comparative approaches to Indonesian regulations and selected international references, including UNCITRAL, OECD, and EU ADR/ODR instruments. The findings show that existing Indonesian regulations have not yet provided enforceable procedural standards for consumer ODR. This gap arises because the relevant norms remain fragmented across the Consumer Protection Law, Trade Through Electronic Systems regulation, Electronic Information and Transactions regime, Electronic Systems and Transactions regulation, Arbitration and Alternative Dispute Resolution Law, and Personal Data Protection Law. Although these legal regimes provide general bases for consumer dispute resolution, electronic documents, electronic systems, alternative dispute resolution, and personal data processing, they do not specifically regulate authority screening, identity and transaction verification, electronic evidence governance, neutral facilitation, outcome documentation, data protection safeguards within ODR proceedings, and post-settlement compliance. The contribution of this article lies not in proposing a new theory of ODR, but in developing a normative-operational reconstruction of consumer ODR through minimum enforceable procedural standards. Through this reconstruction, consumer ODR is positioned not merely as a digital complaint channel, but as an integrated, traceable, and accountable consumer redress mechanism within Indonesia’s digital trade regulatory framework.